Launch of the National Potato and Sweetpotato Development Strategy of Ethiopia - Maru, Joyce; Kirui, Leonard; Saikah, Sheewa; Gebeyehu, Setegn (CGIAR, 2024)
The National Potato and Sweetpotato Development Strategy of Ethiopia was launched in Addis Ababa, Ethiopia. The event was marked with the celebration of the first International Day of Potato on 30th May 2024. The national strategy provides a roadmap for sustainable improvement in the production and productivity of potatoes and sweetpotatoes to improve the livelihoods of farmers, rural communities, and the country’s overall economy.